The “Kaufman system” in the Turkestan general-governorate and the crisis of local administration (1867-1881) - Nurullayev , Jasurbek Khayrulla ugli (The Lingua Spectrum, 2026)
This article provides a detailed analysis of the large-scale administrative reforms implemented between 1867 and 1881 in the Turkestan Governor-Generalship, incorporated into the Russian Empire. Specifically, it examines the fundamental essence of the military-popular administrative system formed under the leadership of the first Governor-General, Konstantin Kaufman. The main focus is on highlighting the deep crisis resulting from the clash between the newly established orders and the local socio-political, economic, and legal structures that had been formed over centuries. Relying on the analysis of existing archival documents and scientific literature, alongside the comparative-historical method, the article reveals the systemic contradictions in introducing the empire’s centralized management model into a region with a distinct culture. It also outlines changes in land-water relations, the tax system, and judicial proceedings, as well as the consequences of artificially subordinating or marginalizing representatives of traditional local governance to the state apparatus. The research results indicate that while the “Kaufman system” was consistent in its internal logic regarding military and political control, the complete lack of mechanisms for coordination with the population’s millennial traditions, Islamic legal orders (Sharia and Adat), and core social institutions not only made an administrative crisis inevitable but also laid the groundwork for future social instability. These conclusions are of significant importance for an objective assessment of the transitional period in the history of the region.